Knockdown of DDX46 Inhibits the Invasion and Tumorigenesis in Osteosarcoma Cells - Jiang, Feng (Oncol Res, 2017)
DDX46, a member of the DEAD-box (DDX) helicase family, is involved in the development of several tumors. However, the exact role of DDX46 in osteosarcoma and the underlying mechanisms in tumorigenesis remain poorly understood. Thus, in the present study, we explored the role of DDX46 in osteosarcoma and the underlying mechanisms. Our results demonstrated that the expression levels of DDX46 in both mRNA and protein were greatly elevated in human osteosarcoma tissues and cell lines. Knockdown of DDX46 obviously inhibited osteosarcoma cell proliferation and tumor growth in vivo. In addition, knockdown of DDX46 also significantly suppressed migration and invasion in osteosarcoma cells. Furthermore, knockdown of DDX46 substantially downregulated the phosphorylation levels of PI3K and Akt in SaOS2 cells. In summary, the present results have revealed that DDX46 plays an important role in osteosarcoma growth and metastasis. Knockdown of DDX46 inhibited osteosarcoma cell proliferation, migration, and invasion in vitro and tumor growth in vivo. Therefore, DDX46 may be a potential therapeutic target for the treatment of osteosarcoma.